Pengaruh Brand Love dan Brand AttachmentTerhadap Repurchase Intention pada Produk Kopi Kenangan di Kota Malang - Berlianda Elsya Putri (Indo Publishing, 2026)
The rapid growth of the coffee shop business in Malang City has led to increasingly intense competition among brands. The high number of available coffee shop options makes it easy for consumers to switch to other brands. Therefore, companies need to build emotional connections with consumers in order to increase repurchase intention. This study aimed to identify and analyze the influence of Brand Love and Brand Attachment on Repurchase Intention for Kopi Kenangan products at the Bondowoso Ruko location in Malang City. This study employeds a quantitative approach with thea survey method. The sample consisted of 100 respondents selected through purposive sampling. The respondents in this study were customers of Kopi Kenangan who had made at least two independent purchases. The data were collected through questionnaires and analyzed with validity tests, reliability tests, classical assumption tests, multiple linear regression, coefficient of determination, t-tests, and F-tests with the aid of SPSS. The results indicated that Brand Love has a significant partial effect on Repurchase Intention, although the direction of the effect is negative. Meanwhile, Brand Attachment has a positive and significant partial effect on Repurchase Intention. Simultaneously, Brand Love and Brand Attachment have a significant effect on Repurchase Intention. This indicates that repurchase intention can be formed through consumers’ fondness for a brand and their emotional attachment to it.